Efficacy of Auditory Training in Elderly Subjects - Morais, Aline Albuquerque; Rocha-Muniz, Caroline Nunes; Schochat, Eliane (Frontiers in Aging Neuroscience, 2015)
Auditory training (AT)  has been used for auditory rehabilitation in elderly individuals and is an effective tool for optimizing speech processing in this population. However, it is necessary to distinguish training-related improvements from placebo and test-retest effects. Thus, we investigated the efficacy of short-term auditory training (acoustically controlled auditory training - ACAT) in elderly subjects through behavioral measures and P300. Sixteen elderly individuals with APD received an initial evaluation (evaluation 1 - E1) consisting of behavioral and electrophysiological tests (P300 evoked by tone burst and speech sounds) to evaluate their auditory processing. The individuals were divided into two groups. The Active Control Group [ACG (n=8)] underwent placebo training. The Passive Control Group [PCG (n=8)] did not receive any intervention. After 12 weeks, the subjects were  revaluated (evaluation 2 - E2). Then, all of the subjects underwent ACAT. Following another 12 weeks (8 training sessions), they underwent the final evaluation (evaluation 3 – E3). There was no significant difference between E1 and E2 in the behavioral test [F(9.6)=0,.6 p=0.92, λ de Wilks=0.65)] or P300 [F(8.7)=2.11, p=0.17, λ de Wilks=0.29] (discarding the presence of placebo effects and test-retest). A significant improvement was observed between the pre- and post-ACAT conditions (E2 and E3) for all auditory skills according to the behavioral methods [F(4.27)=0.18, p=0.94, λ de Wilks=0.97]. However, the same result was not observed for P300 in any condition. There was no significant difference between P300 stimuli. The ACAT improved the behavioral performance of the elderly for all auditory skills and was an effective method for hearing rehabilitation.